Adjuvants for Leishmania vaccines: from models to clinical application - Raman, Vanitha S.; Reed, Steven G.; Duthie, Malcolm S.; Fox, Christopher B.; Matlashewski, Greg (Frontiers in Immunology, 2012)
Two million new cases of leishmaniasis occur every year, with the cutaneous leishmaniasis (CL) presentation accounting for approximately two-thirds of all cases. Despite the high incidence rates and geographic expansion of the disease, CL remains a neglected tropical disease without effective intervention strategies. Efforts to address this deficit have given rise to the experimental murine model of CL. By virtue of its simplicity and pliability, the CL model has been used to provide substantial information regarding cellular immunity, as well as in the discovery and evaluation of various vaccine adjuvants. The CL model has facilitated in vivo studies of the mechanism of action of many adjuvants, including the TLR4 agonist MPL, the TLR7/8 agonist Imiquimod, the TLR9 agonist CpG, adenoviral vectors and the immunostimulatory complexes (ISCOM). Together, these studies have helped to unveil the requirement for certain types of immune responses at specific stages of CL disease and provide a basis to aid the design of effective second-generation vaccines for human CL. This review focuses on adjuvants that have been tested in experimental CL, outlining how they have helped advance our understanding of the disease and ultimately, how they have performed when applied within clinical trials against human CL.